1 Corinthians : an exegetical and contextual commentary - Spurgeon, Andrew B. (Bangalore, India Primalogue Publishing Media Pvt, Ltd., 2012)
The India Commentary on the New Testament (ICNT) series aims to give a well-informed exposition of the meaning of the text and relevant reflections in everyday language from a contemporary Indian context. The intended audience is the theological seminary or bible college, both students and faculty. The commentaries are also ideal for pastors and lay people with an interest in theology or responsibilities for preaching in the local congregation. The commentaries are culturally rooted, and the various applications relating to culture, society, and religious life will help those involved with cross-cultural evangelism and mission work. There is no direct equivalent to the ICNT, and hence, this is the first Indian commentary serving India, the entire subcontinent-India, Nepal, Bangladesh, and Sri Lanka. - back cover.
Introduction -- Commentary -- I. Opening greetings (1:1-9) -- II. The body (1:10-16:18). Paul's responses to Chloe's report (1:10-6:20). Concerning spiritual leaders (1:10-4:21) ; Concerning immorality (5:1-13) ; Concerning lawsuits (6:1-8) ; Concerning visits to prostitutes (6:9-20) ; Conclusion of the First Section : Paul's responses to Chloe's report (1:10-6:20 -- Paul's answers to the Corinthians' questions (7:1-16:18). Concerning the married (7:1-24) ; Concerning the never-been-married (7:25-40) ; Concerning freedom and worship (8:1-11:34) ; Concerning spirit-indwelt people (12:1-15:58) ; Concerning Collection for the Saints (16:1-11) ; Concerning Apollos and others (16:12-18) ; Conclusion of the 'Body' -- III. Concluding greetings (16:19-24).
Includes bibliographical references (pages 193-204).
Keywords: Bible. -- Commentaries; Commentaries